Analisis Kehalalan Daging Sapi Dengan Metode Pork Detection Kit (Pdk) dan Analisis Tingkat Kepedulian Konsumen dalam Mengonsumsi Daging Sapi Halal di Kota Bekasi - Mardiah; Lia Amalia; Trimelati, Dinda Army (JURNAL AGROINDUSTRI HALAL, 2021)
Analysis of the halal beef in Bekasi City Market is essential to find out whether meat traders do adulteration or not. This study aims to determine whether the sold meat contains another meat (wild board/pork) and to determine the level of consumer concern in consuming halal meat in Bekasi City. The method used in this research is the Pork Detection Kit (PDK) method and the survey method using a questionnaire to the community in Bekasi City. The sampling method uses the purposive sampling method. The data analyzed descriptively. The results showed that the beef sold in the Bekasi City market was negative for pork contamination. At the level of consumer concern in consuming halal meat, the results show that 80% of the people in Bekasi City have considered the halal aspect when buying meat for consumption, either fresh meat or frozen meat.